Beyond the Classroom: Integrating the ORID Model for In-Depth Reflection and Assessment in Service-Learning - Fatma Kayan Fadlelmula; Saba Mansoor Qadhi (MDPI AG, 2024)
Service-learning is a community-based learning approach that bridges academic knowledge with practical application through purposeful exploration, action, and reflection. In addition to enhancing academic learning in various disciplines, service-learning cultivates students' self-awareness, personal values, and social responsibility, preparing them with essential skills for life beyond the classroom. However, due to its experiential nature, service-learning presents challenges for effective assessment. This study provides a concrete example of student reflections structured by the Objective, Reflective, Interpretive, and Decisional (ORID) model in practice. Content analysis was implemented by examining undergraduate students' end-of-semester reflection papers while volunteering during the 2022 FIFA World Cup in Qatar. The results showed that the model provided a guided and structured format for students to reflect on their service-learning, going beyond reporting on factual details to engaging in profound reflections on the emotional, cognitive, and prospective aspects. Moreover, with the solution aspect added to the model, students could express their creativity, articulating on innovative solutions they proposed to overcome challenges and how they turned the challenges into favorable outcomes. Clearly, the model stands as a powerful tool for educators, offering deeper insights into students' authentic experiences, fostering comprehensive, critical, and insightful reflection, and thereby facilitating the effective assessment of experiential learning.